Cross-Cultural Validation of the Beck Depression Inventory-II Across US and Turkish Samples - Canel-Cinarbas, Deniz; Cui, Ying; Lauridsen, Erica (Routledge Journals, Taylor & Francis Ltd, 2011)
The purpose of this study was to test the Beck Depression Inventory-II (BDI-II) for factorial invariance across Turkish and U.S. college student samples. The results indicated that (a) a two-factor model has an adequate fit for both samples, thus providing evidence of configural invariance, and (b) there is a metric invariance but no sufficient evidence of scalar invariance across the two groups of students. Testing for differential item functioning (DIF) was also conducted to further investigate the measurement variance of the BDI-II at the item level. Large DIF values were found for 12 items of the BDI-II.
Keywords: Beck Depression Inventory; clinical assessment; factorial invariance; confirmatory factor analysis; culture; diversity issues